The nature of negotiations in face-to-face versus computer-mediated communication in pair interactions. (July 2016) - Rouhshad, Amir; Wigglesworth, Gillian; Storch, Neomy
The Interaction Approach argues that negotiation for meaning and form is conducive to second language development. To date, most of the research on negotiations has been either in face-to-face (FTF) or text-based synchronous computer-mediated communication (SCMC) modes. Very few studies have compared the nature of negotiations across the modes. Such comparisons are important as they can indicate which mode may be more conducive to language learning. The present study set out to compare the nature of negotiations between FTF and SCMC modes in same-proficiency intermediate dyads. Dyads performed two similar decision-making tasks, one in FTF and one in SCMC mode, and were encouraged to provide corrective feedback, where necessary, to their partner. The analysis revealed that negotiations for form and meaning were scarce in both modes, with more negotiations for meaning in FTF mode. The findings also suggested that mode of interaction influenced the type of negotiations, and their outcomes, in terms of modified output as well as successful uptake.